Perancangan Aplikasi Pengelolaan Laporan Kepolisian Studi Kasus Polsek Gatak - Irawan, Selfi Ambar; , Hernawan Sulistyanto, S.T., M.T (2015)
Receipt of reports and complaints from the public is one of the services from police institution. Creation and management of police reports which is manual often hamper Sentra Pelayanan Kepolisian Polsek Gatak to fast and right in handling police reports, including the are no copy of the report data, difficult to data searching on the ledger, and difficult to monitoring the number of reports. Police Reports Management Application is a system to facilitate in making police report in detail and according to standards, regular and complete data management, easy to data searching, monitoring the number of reports, and fast to make a letter. Method of Police Reports Management Application is analysis, which identifies and evaluates all kinds of problems and what requirements expected is. Document analysis is to analyze the documents used by Sentra Pelayanan Kepolisian Polsek Gatak. There are A models, B models, B1 models, and C models reports. The conclusion from this research is to facilitate in police reports data management, police reports making and printing, police reports data searching, and monitoring the number of police reports. Results from this research is a printout of A models, B models, B1 models, C models report, data periodically, and graph the number of incoming reports. Based on the results of the questionnaire can be stated that these applications can be accepted in majority with very satisfy answers through percentage average indication is above 90%.